2012
DOI: 10.1002/adsc.201200096
|View full text |Cite
|
Sign up to set email alerts
|

Dithiolane‐Directed Tandem Oxidation/1,2‐Benzyl Migration of Tetramic Acids under Ambient Conditions

Abstract: Reactions directly involving triplet oxygen are an important issue in organic and biological chemistry. We now report that exposure of tetramic acids in the open air (molecular oxygen) at room temperature can lead to the formation of succinimide derivatives in high to excellent yields via tandem oxidation/1,2‐benzyl migration. In this reaction, the dithiolane moiety plays a crucial role and succinimides are produced either in the presence or absence of dibutyl sulfide as reductant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Recently, we found that tetramic acids 468 bearing a dithiolane moiety in open air (molecular oxygen) can lead to the formation of succinimide derivatives 469 in high to excellent yields. 303 The reaction may proceed via tandem oxidation/1,2-benzyl Scheme 111 Synthesis of a-trifluoromethyl and difluoromethyl carboxylates. migration and the dithiolane moiety is assumed to play a crucial role since the corresponding tetramic acid derivative 475 was inert under the oxidation conditions (Scheme 115).…”
Section: Miscellaneous Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we found that tetramic acids 468 bearing a dithiolane moiety in open air (molecular oxygen) can lead to the formation of succinimide derivatives 469 in high to excellent yields. 303 The reaction may proceed via tandem oxidation/1,2-benzyl Scheme 111 Synthesis of a-trifluoromethyl and difluoromethyl carboxylates. migration and the dithiolane moiety is assumed to play a crucial role since the corresponding tetramic acid derivative 475 was inert under the oxidation conditions (Scheme 115).…”
Section: Miscellaneous Reactionsmentioning
confidence: 99%
“…migration and the dithiolane moiety is assumed to play a crucial role since the corresponding tetramic acid derivative 475 was inert under the oxidation conditions (Scheme 115). 303 Ketene dithioacetals with various dialkylthio groups have been prepared (Fig. 2 and 15) and shown varied specificity.…”
Section: Miscellaneous Reactionsmentioning
confidence: 99%
“…In recent years, this process has received considerable attention, as it can transform readily available cheap aromatic compounds into more complex, functionalized products. A literature survey reveals that dioxygen‐mediated oxidation processes often need the presence of a transition‐metal complex, whereas only a few examples of transition‐metal‐free dioxygen activations are known , . Recently, a photosensitizer (methylene blue, MB) was used to trigger the formation of γ‐hydroxy α,β‐unsaturated γ‐lactams for the reaction of primary amines with various oxidized (by singlet oxygen) furan derivatives [Scheme , [Equation (2)] …”
Section: Introductionmentioning
confidence: 99%
“…In this case, the C–C double bond of the electron-deficient cinnamoyl group of the intermediate B acts as the dienophile, whereas the Ar 1 and C–C double bond of the allene acts as the diene component for the DDA reaction producing intermediate C . This unstable and highly conjugated species then undergoes aromatization via loss of two hydrogen atoms to yield the 3-hydroxy-substituted product 3 in the presence of oxygen atmosphere, whereas the benzo[ f ]-1-indanones 4 are obtained under nitrogen atmosphere.…”
mentioning
confidence: 99%